Support Mechanisms for Women during Menopause: Perspectives from Social and Professional Structures - Alexandra Cristina Cowell; Adam Gilmour; Daniel Atkinson (Women, 2024)
Approximately one billion women globally have undergone menopause, occurring at an age of around 51 years and typically between ages 45 and 54. As life expectancy increases, women are projected to spend at least one-third of their lives in postmenopause, emphasising the growing importance of menopause as a critical public health issue. In this context, this paper aims to offer updated insights into the increasing societal and political interest in menopause. It underscores the impact of support mechanisms encompassing familial, workplace, medical, technological, and government support on women’s attitudes and experiences around menopause. Furthermore, the study aims to identify key gaps in research, practice, or legislation concerning support systems for menopausal women and provide recommendations for enhancing familial, workplace, medical, technological, and government support.